Study on the Effect of Oxygen Defects on the Electrical and Optical Properties of Thin Films - Jeong, Jin (Scanning, 2018)
SnO(2) thin films grown directly on the Si substrate had larger average grain sizes as the power intensity increased, but the average grain size of the SnO(2) thin films grown in oxygen atmosphere decreased as the power intensity increased. Hall measurement of pure SnO(2) thin films showed that the carrier density increased with increasing power. However, upon annealing the SnO(2) thin films, the carrier density decreased with increasing power owing to the formation of oxygen vacancies and the SiO(2) layer between the Si substrate and SnO(2) thin films. The photoluminescence (PL) of the SnO(2) thin film grown in the oxygen atmosphere changed, and it was affected by the oxygen defects at the surface and interfaces of the thin film.